Pengaruh Psikoedukasi terhadap Pengetahuan dan Depresi Orang Tua Anak Retardasi Mental - Bakara, Derison Marsinova; Dahrizal,; Burhan, Rialike (Jurusan Keperawatan FIKES UNSOED, 2014)
Having children with a disorder may can affect stress on families financially, intellectually, socially and physically. Treatments for physical disabilities children resulted a higher depression level than those were not. This pre-eksperimental study apply one group pretest-posttest design. Group of parents of mental retarded children was identified as less knowledge and experiencing depression were exposed to psychoeducation intervention then remeasured after exposing. Sample, 35 people were selected by total sampling. Collected data were analyzed with Wilcoxon test. Results showed significant difference between the level of knowledge and depression after exposed psicoeducation intervention by p=0.00. The results imply to guidelines and standard operating procedures in the management of increased knowledge and reducing depression for mental retarded children parents.